(untitled) (Bangladesh Journal of Child Health, 2019)
Birth defects are one of the leading causes of neonatal mortality worldwide. Every year more than 8.14 million children are born with a serious birth defect. The risk factors predictive of birth defects in babies vary from country to country even from region to region. About 60% of the causes of birth defect in humans are still unknown. However, in about 25% cases, the causes seem to be “multifactorial”, indicating a complex interaction between genetic and environmental risk factors. Many studies have been conducted to determine the association of various risk factors with the incidence of birth defects. Most of them found significant association with maternal age, parity, consanguinity, poor nutrition, life style factors, low socioeconomic condition and many more. But still there is debate in certain issues like common type of birth defect, specific age of mother for having birth defect babies, role of drugs during pregnancy etc. With advancement of diagnostic tools, birth defects can be identified both prenatally and post- natally. This helps further in decision making and planning for both parents as well as physicians to provide accurate treatment in time. Major birth defect babies require intensive care and more hospitalization. Often multidisciplinary approach is essential for them. But till now birth defect cases are neglected in society. Increasing awareness about maternal care during pregnancy, educational programs on birth defect and the consequences of consanguineous marriages need to be highlighted to decrease the incidence of birth defect and their co-morbidities as well as mortality. Bangladesh J Child Health 2019; VOL 43 (1) :49-58